4CPS-082 Evaluation of effectiveness of darunavir/cobicistat monotherapy in hiv patients. (2nd March 2018) - Gómez, P Nieto; Moreno, P; Corpas, M Valle; Hidalgo, I Casas; Delgado, A Rodriguez; Sanchez, R Alvarez; Fernandez, C García
Abstract : Background: HIV therapies are usually based on the action of various antiretroviral drugs coadministered in order to achieve a good virologic (viral loads<50 copies/ml) and immune response (percentage of T CD4 lymphocytes between 32 and 60). In the past few years a single drug therapy based on a protease inhibitor has been used to control HIV infection. Purpose: To analyse the virologic and immune response in patients on darunavir/cobicistat monotherapy. Material and methods: This work is a descriptive observational study. In it, we have made a search of clinical variables as well as the results of analytical tests. The variables included in this study were sex, age, viral loads at the beginning of the treatment and at months 6 and 12, and percentage of T CD4 lymphocytes in blood samples. After that, we performed a statistical analysis. Results: Patients (n=30) had a mean age of 50.2±11.6 years and 66.6% were males. They were all on treatment with a daily tablet of darunavir/cobicistat (800 mg/150 mg) as a single drug for HIV treatment. At the beginning of treatment, 76% of patients had undetectable viral load, at month 6.83% and at month 12.73%. Patients with viral load over 50 copies/ml were 20% at the beginning of treatment, 13% at month 6, and 10% at month 12. Only 50% of patients who began the treatment without virological response could achieve it at month 12. Only 6% of patients with virological response failed it at month 12. In terms of immune response, patients without it at the beginning (percentage of T CD4 lymphocytes below 32%) represented 36.7% and they did not achieve it during 12 months. Every patient with immune response at the beginning of the treatment maintained this response. Only one patient had both virologic and immune failures. Thirty-three per cent of patients had no immune response with virologic response. Conclusion: Based on these findings we can confirm that monotherapy is a great strategy in patients who already have a good control of the HIV infection. Immune and virologic response is difficult to achieve after 12 months in patients who began the treatment without them. No conflict of interest